Draft for internal testing Scientific Committee guidance on appraising and integrating evidence from epidemiological studies for use in EFSA's scientific assessments. (18th August 2020) - ,; More, Simon; Bambidis, Vasileos; Benford, Diane; Bragard, Claude; Hernandez‐Jerez, Antonio; Bennekou, Susanne Hougaard; Koutsoumanis, Kostas; Machera, Kyriaki; Naegeli, Hanspeter; Nielsen, Soren Saxmose; Schlatter, Josef R; et al.
Abstract: EFSA requested its Scientific Committee to prepare a guidance document on appraising and integrating evidence from epidemiological studies for use in EFSA's scientific assessments. The guidance document provides an introduction to epidemiological studies and illustrates the typical biases of the different epidemiological study designs. It describes key epidemiological concepts relevant for evidence appraisal. Regarding study reliability, measures of association, exposure assessment, statistical inferences, systematic error and effect modification are explained. Regarding study relevance, the guidance describes the concept of external validity. The principles of appraising epidemiological studies are illustrated, and an overview of Risk of Bias (RoB) tools is given. A decision tree is developed to assist in the selection of the appropriate Risk of Bias tool, depending on study question, population and design. The customisation of the study appraisal process is explained, detailing the use of RoB tools and assessing the risk of bias in the body of evidence. Several examples of appraising experimental and observational studies using a Risk of Bias tool are annexed to the document to illustrate the application of the approach. This document constitutes a draft that will be applied in EFSA's assessments during a 1‐year pilot phase and be revised and complemented as necessary. Before finalisation of the document, a public consultation will be launched.